Using Prostatic Fluid Levels of Zinc to Bromine Concentration Ratio in Non-Invasive and Highly Accurate Screening for Prostate Cancer - Zaichick Vladimir; Zaichick Sofia (Journal of Hematology and Oncology Research, 2019)
Prostate specific antigen (PSA) does not provide the high reliability and precision that is required for an accurate screening for prostate cancer (PCa). The aim of our study was to search for a simple, rapid, direct, preferably non-invasive, and highly accurate biomarker and procedure for the screening for PCa. For this purpose the levels of bromine (Br) and zinc (Zn) were prospectively evaluated in expressed prostatic fluid (EPF). Also Zn/Br concentration ratio was calculated for EPF samples, obtained from 38 apparently healthy males and from 33, 51, and 24 patients with chronic prostatitis (CP), benign prostatic hyperplasia (BPH) and PCa, respectively. Measurements were performed using an application of energy dispersive X-ray fluorescent (EDXRF) microanalysis developed by us. It was found that in the EPF of cancerous prostates the levels of Zn and Zn/Br were significantly lower in comparison with those in the EPF of normal, inflamed, and hyperplastic prostates. It was shown that “Sensitivity”, “Specificity” and “Accuracy” of PCa identification using the Zn and Zn/Br levels in the EPF samples were all significantly higher than those resulting from of PSA tests in blood serum. It was concluded that the Zn and Zn/Br levels in EPF, obtained by EDXRF, is a fast, reliable, and non-invasive diagnostic tool that can be successfully used by local, non-urologist physicians at the point-of-care to provide a highly effective PCa screening and as an additional confirmatory test before a prostate gland biopsy.
Keywords: Urology Screening